(3GdYed aj GdSLhf (B:s (3OQGSI aj GdfXQjI GdYGeI ddYed aj GdfXe GdYbGHjI (B/ s - (3MSf aDGO YdGes; (3eMehO eMehO eUWais; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 1960)
(3JHOC gPg GdQSGdI HaUd JegjOj Yf UhQ GdYed aj GdfXe GdYbGHjI GdeNJdaI, Ke JfbSe Edi KdGKI CHhGH; MjK jJfGhd GdHGH GdChd GdYed hfXGe GdYbhHI GdSGdHI ddMQjI, Ke GdHGH GdKGfj jJfGhd GdMbhb hGdGdJRGeGJ GdeJYdbI HYed GdSLjf, hCNjQG GdHGH GdKGdK Yf CgOGa GdYed hCSS JfXjeg aj GdSLhf(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1960. s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI UaMGJ (B291 - 297.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdYed aj GdSLhf s; (3JGQjN GdfXe GdYbGHjI s; (3GdfXe GdYbGHjI GdeYGUQIs; (3GdYed GdYbGHjs; (3GdYed GdLHQjs; (3fXGe GdCTZGd GdTGbIs; (3GdVeGfGJ GdGLJeGYjI ddYed HGdSLhfs; (3GdYed hJCgjd GdeSLhfjfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs